2010
DOI: 10.1128/jb.01610-09
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation and Genomic, Nutritional, and Lipid Biomarker Characterization of Roseiflexus Strains Closely Related to Predominant In Situ Populations Inhabiting Yellowstone Hot Spring Microbial Mats

Abstract: Roseiflexus sp. strains were cultivated from a microbial mat of an alkaline siliceous hot spring in Yellowstone National Park. These strains are closely related to predominant filamentous anoxygenic phototrophs found in the mat, as judged by the similarity of small-subunit rRNA, lipid distributions, and genomic and metagenomic sequences. Like a Japanese isolate, R. castenholzii, the Yellowstone isolates contain bacteriochlorophyll a, but not bacteriochlorophyll c or chlorosomes, and grow photoheterotrophically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
87
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 57 publications
6
87
0
Order By: Relevance
“…Because wax esters were not analyzed separately, and wax esters can occur in significant amounts in chlorosomes (15,60), it is possible that some of the alcohols identified might be derived from these components. There is no precedent to suggest that the 14-methyl-pentadecanol (iso-C 16 alcohol) and 15-methylhexadecanol (iso-C 17 alcohol) could be esterifying alcohols for BChls, while they can be prominent components in wax esters of some FAPs (74) and, thus, may be derived from wax esters. Four isoprenoid alcohols were identified, including farnesol (i-C 15:3 -OH), geranylgeraniol (i-C 20:4 -OH), phytol (i-C 20:1 -OH), and phytadienol (i-C 20:2 -OH).…”
Section: Resultsmentioning
confidence: 99%
“…Because wax esters were not analyzed separately, and wax esters can occur in significant amounts in chlorosomes (15,60), it is possible that some of the alcohols identified might be derived from these components. There is no precedent to suggest that the 14-methyl-pentadecanol (iso-C 16 alcohol) and 15-methylhexadecanol (iso-C 17 alcohol) could be esterifying alcohols for BChls, while they can be prominent components in wax esters of some FAPs (74) and, thus, may be derived from wax esters. Four isoprenoid alcohols were identified, including farnesol (i-C 15:3 -OH), geranylgeraniol (i-C 20:4 -OH), phytol (i-C 20:1 -OH), and phytadienol (i-C 20:2 -OH).…”
Section: Resultsmentioning
confidence: 99%
“…Only members of the family of Chloroflexaceae (Chloroflexus aggregans and Roseiflexus spp.) harbor all the genes required to establish the complete 3-hydroxypropionate bi-cycle (22,40,44). Interestingly, Oscillochloris trichoides (also Chloroflexi) possesses only genes encoding malonyl-CoA reductase and propionyl-CoA synthase but lacks genes of the second glyoxylate assimilation cycle (21,25).…”
Section: Vol 77 2011 Coassimilation Of Organic Substrates In Chloromentioning
confidence: 99%
“…Key genes of the autotrophic pathway are indicated by a gray background and genes required for glyoxylate assimilation by a white background. Lowercase represents genes with low identities (less than 40 …”
mentioning
confidence: 99%
“…Genomic and metagenomic analyses of microbial mats in Mushroom Spring and Octopus Spring have demonstrated that Roseiflexus (15,27), but not Synechococcus (28), possesses hydrogenases and might thus produce H 2 by fermentation. The lack of hydrogenases in Synechococcus means that any H 2 produced by Synechococcus nitrogen fixation is lost to the environment where other mat organisms may use it as an electron donor in anoxygenic photosynthesis or respiration.…”
mentioning
confidence: 99%